Target liquid biopsy using “enriched” polymerase chain reaction and DNA melting analysis - I. V. Botezatu; I. O. Panchuk; A. A. Kolomeytseva; A. A. Fedenko; N. N. Mazurenko; I. V. Tsyganova; O. Yu. Susova; V. N. Kondratova; V. P. Shelepov; A. V. Lichtenstein (Успехи молекулярной онкологии)
Objective: to evaluate the possibility of using a highly sensitive method of “enriched” polymerase chain reaction followed by DNA melting analysis (PCR-DMA) for target liquid biopsy of cancer patients.Materials and methods. The “enriched” PCR-DMA was used for mutation scanning of KRAS (codons 12 and 13) in tumor and blood plasma of 20 patients with colorectal cancer.Results. Activated oncogene was found in tumor tissue of 16 patients and in blood plasma of 5 patients (confirmed by sequencing). Mutant KRAS alleles were also found in tumor and plasma of another 2 patients, but in very low concentrations that did not allow their validation by Sanger sequencing. Thus, in our study the target liquid biopsy was successful in ~35 % patients. Since the plasma tests were carried out after repeated medical procedures causing mass death of tumor cells, the actual efficiency of this approach may appear significantly higher.